What is the equation of the normal line of #f(x)= x^2/(x^3− 5x + 1)# at #x = 5#?

Answer 1

Equation of normal line is # y= 13.79x - 68.7#

#f(x)=x^2/(x^3-5x+1) :. f(5)=5^2/(5^3-5*5+1) ~~0.25(2dp) #
Point is at #(x_1,y_1) =(5,0.25)# . Slope is #m= f'(x)#
#f'(x) = (2x*(x^3-5x+1)- x^2(3x^2-5))/(x^3-5x+1)^2#
#f'(x) =m= (25*(5^3-5*5+1)- 5^2(3*5^2-5))/(5^3-5*5+1)^2# or
#m ~~-0.07 #. Slope of normal is #m_1= -1/-0.07~~13.79(2dp)#
Equation of normal line is #(y-y_1)=m_1(x-x_1)# or
#(y-0.25)=13.79(x-5) or y= 13.79x - 68.7# [Ans]
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the equation of the normal line of f(x) = x^2/(x^3 - 5x + 1) at x = 5, we need to determine the slope of the tangent line at x = 5 and then find the negative reciprocal of that slope to obtain the slope of the normal line.

To find the slope of the tangent line at x = 5, we differentiate f(x) with respect to x and evaluate it at x = 5.

Differentiating f(x) = x^2/(x^3 - 5x + 1) using the quotient rule, we get:

f'(x) = (2x(x^3 - 5x + 1) - x^2(3x^2 - 5))/(x^3 - 5x + 1)^2

Simplifying this expression, we have:

f'(x) = (2x^4 - 10x^2 + 2x - 3x^4 + 5x^2)/(x^3 - 5x + 1)^2

Combining like terms, we get:

f'(x) = (-x^4 - 5x^2 + 2x)/(x^3 - 5x + 1)^2

Now, we can evaluate f'(x) at x = 5:

f'(5) = (-5^4 - 5(5)^2 + 2(5))/(5^3 - 5(5) + 1)^2

Simplifying this expression, we have:

f'(5) = (-625 - 125 + 10)/(125 - 25 + 1)^2

f'(5) = (-740)/(101)^2

f'(5) = -0.072871

The slope of the tangent line at x = 5 is -0.072871.

To find the slope of the normal line, we take the negative reciprocal of the slope of the tangent line:

Slope of normal line = -1/(-0.072871) = 13.725

Now, we have the slope of the normal line. To find the equation of the normal line, we use the point-slope form of a line and substitute the values of x = 5 and the slope:

y - y1 = m(x - x1)

Using the point (5, f(5)) on the curve, we substitute x = 5 and y = f(5) into the equation:

y - f(5) = 13.725(x - 5)

Simplifying this equation, we have:

y - f(5) = 13.725x - 68.625

y = 13.725x - 68.625 + f(5)

Therefore, the equation of the normal line of f(x) = x^2/(x^3 - 5x + 1) at x = 5 is y = 13.725x - 68.625 + f(5).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7